PENGARUH LATAR BELAKANG EKONOMI ORANGTUA DAN EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI SMK LABOR BINAAN FKIP UNRI - Ardy ambar saputra; Caska Caska; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Unemployment is one of the main problems that have always faced by each country. Therefore the institution particularly SMK must be capable of setting up and directing its students enter the workforce that has the soul of entrepreneurship. In addition to the factors of the institution in such a personal self efficacy and parental background also affects the students to become entrepreneurs. This research aims to examine the influence of the economic background of the parents and self efficacy entrepreneurship interest efficacy of students. The population of this research are all students of smk labor class XI who got the entrepreneurial subjects as much as 193 students, with the number of samples as much as 115 students. The analysis of the data used is multiple linear regression. The results showed 1) parental economic background is positive and significant effect against the interest in entrepreneurship students, 2) self efficacy are positive and significant effect against the interest in entrepreneurship students, and 3) economic background parents and self-efficacy is simultaneously positive and significant effect against the interest in entrepreneurship students.Key Words: economic background of parents, Self Efficacy, interest in Entrepreneurship